A feature enhancement FCOS algorithm for dynamic traffic object detection - Tuqiang Zhou; Wei Liu; Haoran Li (Connection Science)
The development of object detection plays an important role in the realisation of fully autonomous driving, and the feature extraction is the key step for object detection. There has been significant difference and scale variation of object features for different road traffic participants (RTPs), meanwhile traditional Convolutional Neural Networks (CNNs) was difficult to extract object features efficiently for small targets. In order to improve the ability of feature extraction, a RTP object detection method combining dynamic convolution and feature enhancement was proposed. The Fully Convolutional One-Stage (FCOS) object detection algorithm was used as baseline. First, the dynamic convolution module was designed in the backbone network to identify different object features to the maximum extent. Second, a dual attention module was designed to filter object feature information while reducing the amount of computation. Finally, in the detection part, the feature expression ability of shallow network was further enhanced by multi-scale feature fusion module, and the effectiveness of the proposed algorithm was verified using Cityscapes dataset. The experimental result indicated that mAP increased by 2.3% compared with baseline. This study can improve the efficiency of RTP detection and contribute to the industrialisation of intelligent connected vehicles.